Highly crystalline methylammonium lead tribromide perovskite films for efficient photovoltaic devices - Noel, N; Wenger, B; Habisreutinger, S; Patel, J; Crothers, T; Wang, Z; Nicholas, R; Johnston, M; Herz, L; Snaith, H (American Chemical Society, 2018)
The rise of metal-halide perovskite solar cells has captivated the research community, promising to disrupt the current energy landscape. While a sizable percentage of the research done on this class of materials has been focused on the neat and iodide-rich perovskites, bromide-based perovskites can deliver substantially higher voltages because of their relatively wide band gaps of over 2 eV. The potential for efficient, high-voltage devices makes materials such as these incredibly attractive for multijunction photovoltaic applications. Here, we use the acetonitrile/methylamine solvent system to deposit smooth, highly crystalline films of CH3NH3PbBr3. By using choline chloride as a passivating agent for these films, we achieve photoluminescence quantum efficiencies of up to 5.5% and demonstrate charge-carrier mobilities of 17.8 cm2/(V s). Incorporating these films into photovoltaic devices, we achieve scanned power conversion efficiencies of up to 8.9%, with stabilized efficiencies of 7.6%, providing a simple route to realizing efficient, high-voltage CH3NH3PbBr3 planar-heterojunction devices.